H3K36 Trimethylation-Mediated Epigenetic Regulation is Activated by Bam and Promotes Germ Cell Differentiation During Early Oogenesis in Drosophila - Masanori Mukai; Seiji Hira; Katsuhiro Nakamura; Shoichi Nakamura; Hiroshi Kimura; Masanao Sato; Satoru Kobayashi (Biology Open, 2015)
Epigenetic silencing is critical for maintaining germline stem cells in Drosophila ovaries. However, it remains unclear how the differentiation factor, Bag-of-marbles (Bam), counteracts transcriptional silencing. We found that the trimethylation of lysine 36 on histone H3 (H3K36me3), a modification that is associated with gene activation, is enhanced in Bam-expressing cells. H3K36me3 levels were reduced in flies deficient in Bam. Inactivation of the Set2 methyltransferase, which confers the H3K36me3 modification, in germline cells markedly reduced H3K36me3 and impaired differentiation. Genetic analyses revealed that Set2 acts downstream of Bam. Furthermore, orb expression, which is required for germ cell differentiation, was activated by Set2, probably through direct H3K36me3 modification of the orb locus. Our data indicate that H3K36me3-mediated epigenetic regulation is activated by bam, and that this modification facilitates germ cell differentiation, probably through transcriptional activation. This work provides a novel link between Bam and epigenetic transcriptional control.